The reduction of oocytes and disruption of the meiotic prophase I in Fanconi anemia E-deficient mice. Issue 3 (14th July 2022) - Yin, Huan; Suye, Suye; Zhou, Zhixian; Cai, Haiyi; Fu, Chun
Abstract : In brief: Fanconi anemia results in subfertility and primary ovarian deficiency in females. This study reveals that disrupted meiosis in oocytes is one of the mechanisms involved. Abstract: Fance is an important factor participating in the repair of DNA interstrand cross-links and its defect causes severe follicle depletion in female mice. To explore the underlying mechanisms, we investigated the effects of Fance on ovarian development in embryonic and newborn mice. We found that the number of oocytes was significantly decreased in Fance −/− mice as early as 13.5 days post coitum (dpc). The continuous decrease of oocytes in Fance −/− mice compared with the Fance +/+ mice led to the primordial follicles being almost exhausted at 2 days postpartum (dpp). The mitotic–meiotic transition occurred normally, but the meiotic progression was arrested in pachytene in Fance −/− oocytes. We detected the expressions of RAD51 (homologous recombination repair factor), 53BP1 (non-homologous end-joining repair factor), and γH2AX by immunostaining analysis and chromosome spreads. The expressions of 53BP1 were increased and RAD51 decreased significantly in Fance −/− oocytes compared with Fance +/+ oocytes. Also, the meiotic crossover indicated by MLH1 foci was significantly increased in Fance −/− oocytes. Oocyte proliferation and apoptosis were comparable between Fance −/− and Fance +/+ mice ( P > 0.05). The aberrant high expression at 17.5 dpc and low expressions at 1 and 2 dpp indicated that the expression pattern of pluripotent marker OCT4 (POU5F1) was disordered in Fance −/− oocytes. These findings elucidate that Fance mutation leads to a progressive reduction of oocytes and disrupts the progression of meiotic prophase I but not the initiation. And, our study reveals that the potential mechanisms involve DNA damage repair, meiotic crossover, and pluripotency of oocytes.